Marialva em palavras e imagens : criação e recriação - Ambrosoli, Silvana dos Santos (2010)
The manuscripts of the novel Memorial de Maria Moura by Rachel de Queiroz, are in the Instituto de Letras da Universidade Federal Fluminense. It was published in 1992, and has been the object of students´ research which resulted in various coordinated papers advised by Dr. Marlene Gomes Mendes. The novel was developed in a polyphonic narrative. Marialva, one of its narrators and the protagonist s cousin, narrates her trajectory in six chapters. We apply the Genetic Criticism Methodology which studies the course of creation of a text, in order to trace this written and rewritten character over almost four years of work. This creative process is substantiated on the various steps of the writing process which extends from a velvety covered notebook where the initial ideas were registered to the final manuscript delivered to the publisher. This creative process went through three previous manuscripts with numbered folios and loose pages kept in an envelope showing the author s research for the development of her story and characters. Our work consisted of accompanying Marialva´s elaboration process which in the notebook appears in the form of lists of names for possible characters belonging to the Maria Moura´s group of cousins. Two groups of folios are dedicated to her in the first manuscripts, and in the other steps of the writing process, her story expands to become the narrative voice of six chapters of the novel. We focus on the construction of this text, tracing the course of the author in the exercise of creation through the correction of the manuscripts. We also look at the script and video of the TV miniseries showed by Globo International Network which screenplay was revised by Rachel de Queiroz. Thus the final TV product was also considered allowing a comparison between the novel and the screenplay both developed in words, and the video, Marialva´s visual construction.